2022
DOI: 10.3390/w14142169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three High-Resolution Remote Sensing Precipitation Products on the Tibetan Plateau

Abstract: Remote sensing precipitation products provide rich data for ungauged basins. Evaluating the accuracy and detection capability of remote sensing precipitation products is crucial before application. In this study, an index system in terms of quantitative differences, capturing capacity and precipitation distribution was constructed to evaluate three precipitation products, TRMM 3B42 V7, GPM IMERGE Final and CMORPH V1.0, at various temporal and spatial scales on the Tibetan Plateau from 2001 to 2016. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Ma et al [24] reported that IMERG performs better at elevations of 3000-4000 m, while Zhang et al [13] found differences in the correlation coefficients and relative biases between IMERG and observations at elevations of around 3500 m. Some studies have argued that IMERG performs poorly at high elevations [12,20,21], while others have reported the opposite view [17]. This phenomenon is due to the varying accuracy of the same product in the southern, southeastern, central-eastern, and northeastern TP regions [15]. Moreover, the TP region has complex and heterogeneous terrain with strong local influencing factors.…”
mentioning
confidence: 99%
“…Ma et al [24] reported that IMERG performs better at elevations of 3000-4000 m, while Zhang et al [13] found differences in the correlation coefficients and relative biases between IMERG and observations at elevations of around 3500 m. Some studies have argued that IMERG performs poorly at high elevations [12,20,21], while others have reported the opposite view [17]. This phenomenon is due to the varying accuracy of the same product in the southern, southeastern, central-eastern, and northeastern TP regions [15]. Moreover, the TP region has complex and heterogeneous terrain with strong local influencing factors.…”
mentioning
confidence: 99%